Informativeness of the thrombodynamic method in assessing the state of hemostasis in patients with coronary heart disease - I. F. Shlyk (Медицинский вестник Юга России, 2019)
Objective: to evaluate the information content of the method of thrombodynamics and local indicators of hemostasis system diagnostics in patients with ischemic heart disease.Matherials and methods: 59 people took part in the study, 34 of them made up the main group of patients with coronary artery disease and 25 control group with no coronary artery disease in history. The study participants were once assessed the state of hemostasis using “local” methods and global - Thrombodynamics, according to manufacturers instructions. After evaluating the indicators, the main group of patients was ranked according to the presence of comorbidities.Results: when comparing the hemostasiogram indicators between the main group and the control group, no significant differences were found. Evaluating the indicators of thrombodynamics - there is a statistically significant increase in the blood thrombogenic potential in the main group.Conclusions: in patients with coronary artery disease, in order to timely detect hemostasis disorders, an integrated approach is needed, consisting not only in conducting local tests of the study, but also global ones.